Hydrocephalus and shunts: a comparative flow-pressure study - Angelo Luiz Maset; Matheus Fernando Manzolli Ballestero; Dionei Freitas de Moraes (Brazilian Society for Pediatric Neurosurgery, 2021)
Introduction: Differential Pressure Shunts (DPS) for hydrocephalus work through a pressure differential between the proximal and the distal inlet. Neurosurgeon's reference is extra-low, low, medium, normal or high-pressure valves, symbolizing the shunt's resistance against the downstream flow. The Brazilian manufacturing process for all shunts is regulated by ISO 7195 version 2006, revised in 2016, and it allows a lot of flexibility in the determination of shunt resistance and flow characteristics. Methods: This article compares the pressure-flow characteristics of some hydrocephalus shunts available in Brazil based on their information brochures Results: Six shunt information brochures were compared regarding to CSF flow-control manufacturing graphs and/or pressure work range tables. Based on the data obtained of each valve, authors propose and introduce a comparative table that can be helpful if used as a guide to the neurosurgeon when one considers either a first time shunt implantation or a shunt revision Conclusion: There is no standardization regarding the pressure which defines the different models of shunts available in Brazil and neurosurgeon must be aware when choosing a specific shunt and even more when, in a shunt review, choose another manufacturer.